Role of Ephedrine for Management of Hypotension During Spinal Anaesthesia for Caesarean Delivery (Journal of the Bangladesh Society of Anaesthesiologists, 2018)
Background: Hypotension during spinal anaesthesia for caesarean section remains a common scenarioin our clinical practice. Certain risk factors play a role in altering the incidence of hypotension. Ephedrinehas been the drug of choice for more than 30 years in the treatment of spinal anesthesia induced maternalhypotension. It has a good safety record, ready availability, and familiarity to most anesthesiologists.Aims: To determine the efficacy and safety of prophylactic bolus dose of 0.5 mg/kg intravenous ephedrinefor the prevention of hypotension during spinal anesthesia for cesarean delivery.Methods: It was designed a randomized, double-blinded study. Patients were randomly allocated intotwo groups: ephedrine group (n=30) and control group (n=30). Intravenous preload of 15 mL/kg lactatedRinger’s solution was given. Shortly after the spinal injection, ephedrine0.5 mg/kg or saline was injectedintravenous for 60 sec.Results: The mean of highestand lowest heart rate in the ephedrine group was higher than those ofcontrol group (p